Urban research in film using walking tours and psychogeographic approaches - Aled Singleton (Visual Studies, 2024)
This article investigates urban change, making films from research approaches which use ethnographic walking interviews, public walking tours and psychogeographic techniques. The case study focuses on Newport, South Wales, UK. Using this example, I explore the longer-term impacts of the (mostly) state-led reconfiguration of British towns and cities from the late-1950s to the mid-1970s. Contemporary film for this period sets the context and links to Guy Debord’s concept of psychogeography, psychogeography in film, and associated walking techniques. This article builds a methodology from these principles, where one-to-one participant-led walking interviews – both outdoor and using online maps – reacquaint people over aged 55 with earlier periods of their biographies. These approaches reveal deeply-held memories and articulate feelings relevant to the present and future. This article develops and analyses practice, offering ways to film walking tours to sensitivity present and explore place narratives over time: firstly, working with community activists to reveal the politics of local housing; and secondly, a commission with a theatre company where three artists follow a specific walking route which explores urban change and rights to the city. As towns and cities face challenges these approaches offer visual methods to engage the public in place making.